The lived experiences of rural HIV social workers. Issue 1 (2nd January 2023) - Owens, Christopher; Voorheis, Eva; Lester, Jessica N.; Green, Harold D.; Herbenick, Debby; Dodge, Brian; Hubach, Randolph D.
ABSTRACT: HIV service providers are the primary implementers of HIV care services, but rural HIV service providers are under researched. We used an interpretative phenomenological analysis to explore rural HIV service providers' lived experiences of working in HIV care, who work in a rural region of a Midwestern state in the United States. From July to August 2019, 15 HIV service providers participated in a one-hour semi-structured telephone interview that elicited their experiences working in the rural HIV care continuum. Participants were tired of constantly educating and working to reduce HIV stigma; however, they received support from family and friends once they educated them about HIV. Participants felt they lacked control over systems and they developed emotional-based coping to address constant occupational stressors. Findings highlight the importance of resiliency and advocacy research and practice across ecological levels.